Measurement of the top quark pair production cross section in the lepton+jets channel in proton-antiproton collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (My University, 2011)
We present a measurement of the inclusive top quark pair production cross section in pp̄ collisions at √s=1.96TeV utilizing data corresponding to an integrated luminosity of 5.3fb-1 collected with the D0 detector at the Fermilab Tevatron Collider. We consider final states containing one high-pT isolated electron or muon and at least two jets, and we perform three analyses: one exploiting specific kinematic features of tt̄ events, the second using b-jet identification, and the third using both techniques to separate the tt̄ signal from the background. In the third case, we determine simultaneously the tt̄ cross section and the ratio of the production rates of W+heavy flavor jets and W+light flavor jets, which reduces the impact of the systematic uncertainties related to the background estimation. Assuming a top quark mass of 172.5 GeV, we obtain σtt̄=7.78-0.64+0.77pb. This result agrees with predictions of the standard model. © 2011 American Physical Society.